Is research with qualitative data more prevalent and impactful now? Interviews, case studies, focus groups and ethnographies - Thelwall, Mike; Nevill, Tamara (Library & information science research, 2021)
With qualitative research apparently threatened by big data, researchers, editors, educators, librarians, and publishers need to understand the mix of research methods used in their field to guide decision making. In response, this study assesses the prevalence and citation impact of academic research between 1996 and 2019 that reports one of four common methods to gather qualitative data: interviews, focus groups, case studies, and ethnography. With minor exceptions, the prevalence of qualitative data has increased, often substantially, since 1996. In addition, all 27 broad fields (as classified by Scopus) now publish some qualitative research, with interviewing being by far the most common approach. The citation impact of interview and focus group research mostly decreased over time, whereas of case study citation impact increased, and ethnography was above average in its two core subject areas. This suggests that methods teachers, researchers, editors, librarians, and publishers should be increasingly open to the value of qualitative data. •Studies using interviews, case studies, focus groups or ethnography were compared in Scopus articles from 1996 and 2019.•Qualitative research became more common in all broad fields between 1996 and 2019.•Ethnography became more common between 1996 and 2019 and is most used in the social sciences, arts and humanities.•Interviews became more common in all broad fields between 1996 and 2019.•The citation impact of research with interviews decreased from 1996 to 2019.